"Traditional" Resolution of Land Conflicts: The Survival of Precolonial Dispute Settlement in Burundi. (November 2017) - De Juan, Alexander
Where and how have precolonial institutions of conflict resolution remained intact? Although it is often argued that "traditional" institutions can play a key role in managing communal conflicts, little is known about the conditions of their "survival." This article argues that historical, political, and cultural topographies are essential to understanding patterns of the persistence and demise of precolonial institutions. Traditional modes of conflict resolution remain strong where they have been internalized over centuries: in the cultural and political centers of precolonial states. I use original geocoded survey data and historical spatial information on precolonial Burundi to analyze this hypothesis. The estimations yield robust correlations between the geographic patterns of the precolonial kingdom and current modes of resource-related conflict resolution.